Bombyx mori Flap endonuclease 1 correlates with the repair of ultraviolet-induced DNA damage. (October 2022) - Tang, Qi; Liu, Yue; Liu, Yutong; Zhu, Feifei; Yu, Qian; Chen, Huiqing; Chen, Liang; Ma, Shangshang; Xu, Huixin; Chen, Keping; Li, Guohui
Graphical abstract: Abstract: Solar ultraviolet radiation (UV) can cause DNA damage in microorganisms. Flap endonuclease 1 (FEN1) is a structure-specific nuclease and plays important roles in DNA replication and repair. At present, the properties and functions of FEN1 have not been characterized in detail in invertebrates such as Bombyx mori . In this study, Bombyx mori FEN1 (BmFEN1) was expressed in E. coli, and was shown to have nuclease activity that nonspecifically cleaved DNA in vitro . However, inside the cell, BmFEN1 did not cleave DNA randomly. Truncated BmFEN1 missing the nuclear localization signal (346–380 aa) still had the nuclease activity, but was no longer precisely localized to the sites of UV-induced DNA damage. It was further found that BmFEN1 favored the faster repair of UV-damaged DNA. The present study will provide a reference for further understanding the functions of BmFEN1 and UV-induced DNA damage repair mechanisms in insects.